MOBILE OFFLOADING USING POWER BASED DECISION IN WIRELESS COMMUNICATION - M.Nivethamani, Soma Prathinha (International Journal of Research Science and Management, 2015)
The cognitive radio techniques are integrated to offload the mobile traffic from mobile Base Stations (BSs) to Internet Service Providers (ISPs). Finding the solution for the mobile offloading has been a topical in recent years. Hence in wireless networks to improve the energy efficiency it is essential to analyze and optimize the power utilization and bandwidth allocation. Therefore the proposed system presents a power based decision algorithm in which offloading is done by choosing the energy efficient Wi-Fi Access Point. The user Filtration technique will offload the user to Wi-Fi Access Point by considering the bandwidth allocated for the services and the SBS (Secondary Base Station) bandwidth.